Create a Country Perception and Image by International Public Relations: An Empirical Research about Perception and Image of Turkey in Germany (2010-2013) - ÖZDEMİRCİ, ATA (ANKARA UNIV EUROPEAN UNION RESEARCH CENTRE, 2018)
For centuries, countries have always communicated with each other, such as wars, political and economic power struggles, outbreaks, migrations, border changes, technical developments. This communication is sometimes caused by reasons such as political or economic power struggles. Today, countries have to deal with the developments, trade, social, cultural exchanges that are happening within the borders of each other. It is necessary for one country to have a good place in the international arena. Counties need to gain a positive place in international communication. Providing a positive perception in the international arena will feed countries in commercial, economic and political sense. Positive perception will lead to greater investment in the country, increased cooperation and ultimately achieving country interests at the final point.
Keywords: International public relations; country perception; country image